Cholesterol transfer via endoplasmic reticulum contacts mediates lysosome damage repair. (21st November 2022) - Radulovic, Maja; Wenzel, Eva Maria; Gilani, Sania; Holland, Lya KK; Lystad, Alf Håkon; Phuyal, Santosh; Olkkonen, Vesa M; Brech, Andreas; Jäättelä, Marja; Maeda, Kenji; Raiborg, Camilla; Stenmark, Harald
Abstract: Lysosome integrity is essential for cell viability, and lesions in lysosome membranes are repaired by the ESCRT machinery. Here, we describe an additional mechanism for lysosome repair that is activated independently of ESCRT recruitment. Lipidomic analyses showed increases in lysosomal phosphatidylserine and cholesterol after damage. Electron microscopy demonstrated that lysosomal membrane damage is rapidly followed by the formation of contacts with the endoplasmic reticulum (ER), which depends on the ER proteins VAPA/B. The cholesterol‐binding protein ORP1L was recruited to damaged lysosomes, accompanied by cholesterol accumulation by a mechanism that required VAP–ORP1L interactions. The PtdIns 4‐kinase PI4K2A rapidly produced PtdIns4P on lysosomes upon damage, and knockout of PI4K2A inhibited damage‐induced accumulation of ORP1L and cholesterol and led to the failure of lysosomal membrane repair. The cholesterol–PtdIns4P transporter OSBP was also recruited upon damage, and its depletion caused lysosomal accumulation of PtdIns4P and resulted in cell death. We conclude that ER contacts are activated on damaged lysosomes in parallel to ESCRTs to provide lipids for membrane repair, and that PtdIns4P generation and removal are central in this response. Synopsis: Lysosome integrity is essential for cell survival, and ruptures in lysosome membranes are repaired by the ESCRT machinery. This study identifies an additional, ESCRT‐independent repair mechanism that involves cholesterol transfer mediated by contact sites between lysosomes and the endoplasmic reticulum (ER). Upon lysosome damage, the ER proteins VAPA/B form contacts between ER and lysosomes and recruit the cholesterol‐binding protein ORP1L. PI4K2A‐dependent accumulation of PtdIns4P on the damaged lysosomes is essential for ORP1L recruitment and lysosome repair. ORP1L induces cholesterol accumulation on damaged lysosomes. Depletion of the cholesterol–PtdIns4P transporter OSBP causes PtdIns4P hyperaccumulation on damaged lysosomes and impairs cell viability. Abstract : The cholesterol‐binding protein ORP1L mediates ESCRT‐independent lysosome damage repair via contact sites between lysosomes and the endoplasmic reticulum.